10 Outcomes of Patients with Renal Cell Carcinoma Achieving Pathologic Complete or Major Response After Consolidative Nephrectomy Following Immune Checkpoint Inhibitor Therapy - Paulo Siqueira do Amaral; Rohit Mehra; Jennifer B Gordetsky; Tian Zhang; Payal Kapur; James Brugarolas; Wadih Issa; Shahed Abdullah; Ulka N Vaishampayan; Laura Wood; Rana R McKay; Justine A Panian; et al. (The Oncologist, 2026)
Abstract Background Select patients with locally advanced or metastatic renal cell carcinoma (RCC) are candidates for consolidative nephrectomy (CN) following immune checkpoint blockade (ICB). Existing cohorts have been limited by heterogeneous pathological assessment and small sample sizes, limiting validation of pathological biomarkers that could inform patient selection and post-operative management. We examined the association of pathologic complete response (pCR) and major pathologic response (MPR) with clinical outcomes in patients undergoing deferred CN after ICB. Methods We conducted a retrospective multicenter study including patients with locally advanced or metastatic RCC who underwent deferred CN following ICB between 2015 and 2025 at seven US institutions. Clinical and pathological data were collected at baseline and during follow-up. Pathology assessment was performed by dedicated genitourinary pathologists. The primary endpoint was 18-month progression-free survival (PFS), estimated by the Kaplan–Meier method with 95% confidence intervals calculated by Greenwood’s variance formula and p-value were estimated with z-test, in the overall cohort and in subgroups stratified by pCR (no residual viable tumor), MPR (residual viable tumor up to 10%), sarcomatoid differentiation, and pathologic nodal involvement. Secondary endpoints included 18-month overall survival (OS) and objective response rate evaluated in the primary tumor, metastatic sites, and overall (combined) per RECIST 1.1. PFS was defined as the time from surgery to progression, death, or last follow-up; OS was defined as the time from surgery to death or last follow-up. Results total of 217 patients were included with a median follow-up of 35 months (IQR 20 – 53) from start of ICB and 22 months (IQ 10-42) from CN. Median age was 62 years, 77% male, 85% White and 71% IMDC intermediate-risk. At treatment initiation, 77% had M1 disease and 87% had clear cell histology. Preoperative regimens included dual ICB (39%), ICB plus TKI (56%), and ICB monotherapy (5%) with a median duration of 5.6 months (IQR 2.8 – 11.2) prior to surgery. Pathological assessment demonstrated pCR in 13% and MPR in 31%. Sarcomatoid features were present in 19% of patients; 15% had pathological nodal involvement. The 18-month PFS was 56.6% (95% CI 49.3 – 63.9%) in the entire cohort. Patients with pCR had significantly improved 18-month PFS compared to those without (100% vs. 49.6%; p < 0.01) as did those with MPR (67.2% vs. 50.8%; p = 0.03). The overall 18-month OS was 82.6% (95% CI 76.9–88.3%) and was higher in patients with pCR (100% vs. 79.8%; p < 0.001) but did not differ by MPR status (82.2% vs. 82.3%; p = 0.99. Following delayed CN, 53% resumed ICB, 12% discontinued due to toxicity, 26% electively discontinued (shared decision or ≥ 2 years of ICB), and 9% due to disease progression. Conclusions Pathologic complete response following CN after ICB is associated with improved PFS and OS. These findings support pCR as a promising biomarker and may guide post-operative management strategies.